Long-term outcomes and disease course of children with juvenile idiopathic arthritis in the ReACCh-Out cohort: a two-centre experience. (13th May 2020) - Chhabra, Amieleena; Robinson, Cal; Houghton, Kristin; Cabral, David A; Morishita, Kimberly; Tucker, Lori B; Petty, Ross E; Larché, Maggie; Batthish, Michelle; Guzman, Jaime
Abstract: Objective: To assess long-term outcomes of children with JIA diagnosed in the biologic era. Methods: Chart review of patients prospectively enrolled in the Research in Arthritis in Canadian Children Emphasizing Outcomes inception cohort at two Canadian centres. Inactive disease and remission were defined according to Wallace criteria. Results: We included 247 of 254 (97%) eligible patients diagnosed 2005–10. At the last follow-up visit at a median age of 16.9 years, 47% were in remission off medications, 25% in remission on medications and 27% had active disease; 51% were on at least one anti-rheumatic medication (22% on biologics). Patients with systemic JIA had the highest frequency of remission off medications (70%) and patients with RF-positive polyarthritis had the lowest (18%) ( P  <0.05 by Fisher's exact test). Among 99 patients with oligoarthritis at enrolment, 14 (14%) had an oligoarthritis extended course. Forty-five patients (18%) had at least one erosion or joint space narrowing in X-rays or MRI, and two (0.8%) required joint replacement. Conclusion: Relative to historical cohorts, this study suggests a reduction in JIA permanent damage, a more favourable prognosis for systemic JIA and a lower progression to oligoarthritis extended category. However, in an era of biologic therapy, one in four patients with JIA still enter adulthood with active disease and one in two still on treatment.